Recent Advances in MXene-Based Electrochemical Sensors - Ziyi Zhao; Jiayi Cao; Boyu Zhu; Xinru Li; Lin Zhou; Bin Su (Biosensors)
MXene is a new family of two-dimensional nanomaterials with outstanding electrical conductivity, tunable structure, biocompatibility, and a large surface area. Thanks to these unique physicochemical properties, MXene has been used for constructing electrochemical sensors (MECSens) with excellent performance. In particular, the abundant surface termination of MXene can contribute to greatly enhancing the analytical sensitivity and selectivity of MECSens. Recently, MECSens have been widely applied in many fields including clinical diagnosis, infectious disease surveillance, and food security. However, not all MXene materials are suitable for building electrochemical sensors. In this article, we present an overview of different MECSens that have been developed so far. We begin with a short summary of the preparation and characterization of MECSens. Subsequently, the electrochemical performance, detection strategies, and application scenarios of MECSens are classified and briefly discussed. The article ends with a short conclusion and future perspectives. We hope this article will be helpful for designing and constructing MECSens with outstanding activity for electrochemical analysis.